Solid State Kinetics of Palladium-N-(2-benzothiazolyl)-Thiourea Complex from T.G. Analysis - Verma, U.N.; Singh, Bhola (Asian Journal of Chemistry, 2010)
Palladium chloride from a 1:2 complex with N-(2-benzothiazolyl)-thiourea. It undergoes a four steps decomposition. The complex decomposes regularly without any distinguishable rest with random nucleation mechanism. Kinetic parameters like apparent activation energy, frequency factor, activation entropy and apparent order of reaction have been detennined employing the grapbical method of Freeman and Carroll and Doyle method as modified by Zsako introducing standard deviations in the calculation.